Clarice Lispector and the Novel - Arranz, Manuel [UNESP] (Univ Estadual Paulista, Fundacao Editora Unesp, 2015)
This article studies the novel creation process of Clarice Lispector, observing the connection between the main themes in Clarice's work, and the formal research done by the author. The following novels support our reflections: A Breath of Life: Pulses; The Passion According to G. H.; The Hour of the Star; An Apprenticeship or The Book of Delights.
Keywords: Clarice Lispector; Form; Language; Novel; Writing